Digital Era Leadership of School Administrators under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office - มีทองแสน โชติมณี; ชวศิริกุลฑล นันทนา; ประเสริฐสิน อัจศรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) examine the level of digital leadership among school administrators; (2) compare digital leadership levels based on gender, educational attainment, work experience, and school size; and (3) investigate guidelines for developing digital leadership among school administrators. The sample comprised 151 school administrators under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office during the 2025 academic year. The research instrument was a five-point Likert scale questionnaire. The Index of Item-Objective Congruence (IOC) ranged from 0.80 to 1.00, and the reliability coefficient was 0.98, indicating high internal consistency. The data were analyzed using frequency, percentage, mean, standard deviation, independent samples t-test, and one-way ANOVA (F-test). In addition, semi-structured interviews were conducted, and the qualitative data were analyzed using content analysis. The results indicated that: (1) The overall level of digital leadership among school administrators, as well as across all dimensions, was at the highest level (x̄ = 4.55, SD = 0.216). Among the dimensions, digital technology competency had the highest mean score (x̄ = 4.57, SD = 0.265), also at the highest level. (2) There were no statistically significant differences in digital leadership levels when classified by gender, educational attainment, work experience, and school size. (3) The guidelines for developing digital leadership suggested that administrators should formulate a clear digital vision and strategies aligned with the school context, act as role models in technology utilization, enhance digital competencies for effective management, promote ethical and responsible digital citizenship, and establish collaborative learning networks. These approaches are essential for fostering a learning-oriented organizational culture and driving innovation within educational institutions.